The making of an octopus arm - Nödl, Marie-Therese (EvoDevo, 2015)
BACKGROUND: Most of our current findings on appendage formation and patterning stem from studies on chordate and ecdysozoan model organisms. However, in order to fully understand the evolution of animal appendages, it is essential to include information on appendage development from lophotrochozoan representatives. Here, we examined the basic dynamics of the Octopus vulgaris arm’s formation and differentiation - as a highly evolved member of the lophotrochozoan super phylum - with a special focus on the formation of the arm’s musculature. RESULTS: The octopus arm forms during distinct phases, including an early outgrowth from an epithelial thickening, an elongation, and a late differentiation into mature tissue types. During early arm outgrowth, uniform proliferation leads to the formation of a rounded bulge, which subsequently elongates along its proximal-distal axis by means of actin-mediated epithelial cell changes. Further differentiation of all tissue layers is initiated but end-differentiation is postponed to post-hatching stages. Interestingly, muscle differentiation shows temporal differences in the formation of distinct muscle layers. Particularly, first myocytes appear in the area of the future transverse prior to the longitudinal muscle layer, even though the latter represents the more dominant muscle type at hatching stage. Sucker rudiments appear as small epithelial outgrowths with a mesodermal and ectodermal component on the oral part of the arm. During late differentiation stages, cell proliferation becomes localized to a distal arm region termed the growth zone of the arm. CONCLUSIONS: O. vulgaris arm formation shows both, similarities to known model species as well as species-specific patterns of arm formation. Similarities include early uniform cell proliferation and actin-mediated cell dynamics, which lead to an elongation along the proximal-distal axis. Furthermore, the switch to an adult-like progressive distal growth mode during late differentiation stages is reminiscent of the vertebrate progress zone. However, tissue differentiation shows a species-specific delay, which is correlated to a paralarval pelagic phase after hatching and concomitant emerging behavioral modifications. By understanding the general dynamics of octopus arm formation, we established a basis for further studies on appendage patterning, growth, and differentiation in a representative of the lophotrochozoan super phylum. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13227-015-0012-8) contains supplementary material, which is available to authorized users.